AmpC β-Lactamase Variable Expression in Common Multidrug-Resistant Nosocomial Bacterial Pathogens from a Tertiary Hospital in Cairo, Egypt - Aliaa Ali El Shamy; Zainab Zakaria; Mahmoud M. Tolba; Nermeen Salah Eldin; Al-Taher Rabea; Mahmoud M. Tawfick; Hebatallah A. Nasser (International Journal of Microbiology)
The emergence of AmpC (pAmpC) β-lactamases conferring resistance to the third-generation cephalosporins has become a major clinical concern worldwide. In this study, we aimed to evaluate the expression of AmpC β-lactamase encoding gene among the pathogenic Gram-positive and Gram-negative resistant bacteria screened from clinical samples of Egyptian patients enrolled into El-Qasr El-Ainy Tertiary Hospital in Cairo, Egypt. A total of 153 bacterial isolates of the species Pseudomonas aeruginosa, Klebsiella pneumoniae, and Enterococcus faecium were isolated from patients diagnosed with urinary tract infection (UTI), respiratory tract infection (RTI), and wound infections. The total number of E. faecium isolates was 53, comprising 29 urine isolates, 5 sputum isolates, and 19 wound swab isolates, whereas the total number of P. aeruginosa isolates was 49, comprising 27 urine isolates, 7 sputum isolates, and 15 wound swab isolates, and that of the K. pneumoniae isolates was 51, comprising 20 urine isolates, 25 sputum isolates, and 6 wound swab isolates. Our results indicated that there is no significant difference in the expression of AmpC β-lactamase gene among the tested bacterial species with respect to the type of infection and/or clinical specimen. However, the expression patterns of AmpC β-lactamase gene markedly differed according to the antibacterial resistance characteristics of the tested isolates.